Epidemiology, Treatment Patterns, and Outcomes of Metastatic Soft Tissue Sarcoma in a Community-Based Oncology Network. (29th December 2013) - Chen, Clara; Borker, Rohit; Ewing, James; Tseng, Wan-Yu; Hackshaw, Michelle D.; Saravanan, Shanmugapriya; Dhanda, Rahul; Nadler, Eric
Abstract : Purpose . To assess epidemiology, treatment patterns, and outcomes of metastatic soft tissue sarcoma (mSTS) patients in USA community oncology practices. Methods . This retrospective, descriptive study used US Oncology's iKnowMed electronic health records database. Adults (≥18 years) with mSTS and at least two visits between July 2007 and June 2010 were included. Key outcomes were practice patterns, overall survival (OS), and progression-free survival (PFS). Results . 363 mSTS patients (174 treated and 189 untreated) met the prespecified exclusion/inclusion criteria. The most common subtypes were leiomyosarcoma (n = 104 ; 29%), liposarcoma (n = 40 ; 11%), and synovial sarcoma (n = 12 ; 3%); the remainder (n = 207 ; 57%) comprised 27 histologic subtypes. Treated patients were younger and had lower ECOG scores; 75% and 25% received first-line combination or monotherapy, respectively. Median OS of treated and untreated patients was 22 and 17 months, respectively, and 29 months in patients with the three most common subtypes. Before controlling for effects of covariates, younger age and lower ECOG scores were associated with better OS and PFS. Conclusion . This study provides insights into mSTS epidemiology, treatment patterns, and outcomes in a large community-based oncology network. These results warrant further studies with larger cohorts.